Issues in Broadcasting and Technological Determinism: A Review - Madaki, Willaim Musa; Kaigama, Kwapsoni Pius; Ayagwa, Famous Nengem (International Journal of Humanities, Education, and Social Sciences, 2024)
This paper explored critical issues in broadcasting through the lens of technological determinism, acknowledging its role in shaping the present landscape while calling for a cautious evaluation of its consequences. The paper utilised the Technological Determinism Theory to explain the topic and employed a qualitative research method, gathering data from secondary sources like textbooks, internet materials, journal articles, and websites. The study found that the landscape of broadcasting has undergone significant transformations in recent years, driven by advancements in technology. These changes have brought forth a multitude of issues that impact both media organizations and society at large. To address these challenges, media organizations and policymakers must collaborate to strike a balance between embracing technological advancements and upholding principles of diversity, accuracy, and societal well-being. The study concludes that it is essential to recognize the agency of human decisions in shaping broadcasting practices rather than being solely driven by technological forces to navigate the future of broadcasting responsibly and sustainably.